Perbandingan Financial Distress Bank Syariah Di Indonesia Dan Bank Islam Di Malaysia Sebelum Dan Sesudah Krisis Global 2008 Menggunakan Model Altman ZScore - Siti Zulaikah; Nisful Laila (Universitas Airlangga, 2016)
This study aims to find out the comparison between the prediction of financial distress of Islamic Banks in Indonesia and that of Islamic Banks in Malaysia before and after the global crisis 2008 using quantitative method and purposive sampling. The prediction of financial distress was done by using Altman Z-score measuring. The technique used to examine the financial distress is Mann-Whitney, and for those after the crisis were examined using Independent sample T-test. The result of this research shows that there is a significant difference between Islamic banks in Indonesia and those in Malaysia either before or after the global crisis 2008 with 5% significance level. The Islamic banks in Indonesia are in secure zone either before or after the crisis. However, the Islamic banks in Malaysia are in grey areawhich cannot be made sure of the bankruptcy either before or after the crisis.